Produção de energia e seus impactos socioeconômicos: o caso da usina termelétrica Porto do Itaqui - SILVA, Clelton dos Santos da (2025)
The energy transition represents a vital strategy to mitigate environmental, economic and social impacts resulting from dependence on fossil fuels. It is a reality for some economies that seek to transition to clean energy sources in favor of a sustainable future for the planet. The analysis of the socioeconomic impacts of electricity production is essential, especially when considering the use of fossil fuels. This energy source, although still predominant, has significant consequences for public health, the environment and the economy. The burning of fossil fuels emits greenhouse gases, which are responsible for global warming, in addition to atmospheric pollutants that affect air quality and human health. The Growth Acceleration Program (PAC) initially proposed the implementation of the Porto Itaqui Thermoelectric Plant, presented by the Federal Government as a strategic project to boost the socioeconomic development of the industrial region of São Luís, Maranhão. This study analyzes the impacts of the thermoelectric plant on the rural communities of Vila Maranhão, São Benedito, Cajueiro and Camboa dos Frades, investigating its influence on local economic activities, effects on the quality of life of residents and environmental impacts. The objective is to evaluate the contribution of the thermoelectric plant to local development, considering economic, social and environmental aspects. The qualitative methodology used included a literature review, document analysis and semi-structured questionnaires. The results can highlight the extent of the social and environmental impacts that occurred during the installation process until the operation of the project, such as air pollution and environmental degradation, in addition to negative effects on the quality of life of residents. Socioeconomic development was limited, differing from the expected results, with few employment and income opportunities. The lack of government support for the affected communities was also evidenced and is part of the region's problems. The results found are at odds with what is proposed by the United Nations (UN) assessments. Based on studies on general aspects related to the generation of electricity using coal and the specific study, we conclude that the energy transition is essential to minimize environmental and social impacts. Brazil must intensify efforts to prioritize renewable sources throughout its territory and reduce the use of coal. In addition, a collaborative approach between governments, companies and civil society is crucial to pave the way for an effective energy transition.